Criminal Liability For Dark Pattern Practices In Personal Data Processing - Yusuf Bagus Febrianto; Selamat Widodo; Yusuf Saefudin (Journal of Law and Policy Transformation, 2025)
This study examines criminal liability for the use of dark patterns in the registration process on digital platforms and applications, which often mislead users into providing consent for the processing of their personal data. Dark patterns are interface design strategies intentionally crafted to influence user behavior through visual and psychological manipulation, resulting in consent that is no longer freely given. The purpose of this research is to analyze the basis of criminal liability for the implementation of dark patterns under Indonesia’s national legal framework, particularly the Personal Data Protection Law (PDP Law), the Electronic Information and Transactions Law (ITE Law), and the 2023 Criminal Code (KUHP), as well as to identify obstacles to law enforcement against such practices in Indonesia. This study employs a normative legal research method using statutory, conceptual, and case approaches. The findings indicate that dark patterns may fulfill the elements of a criminal offense due to the presence of intentionality, deception, and unlawful economic gain, thereby allowing liability to be imposed on both individuals and corporations. Nevertheless, significant barriers to effective enforcement remain, including the absence of an independent data protection authority, the lack of clear legal standards regarding manipulative interface design, and low levels of digital literacy among the public. This research underscores the urgency of strengthening regulatory frameworks and institutional capacity to ensure the protection of privacy rights and legal certainty within Indonesia’s digital ecosystem. Keywords: Dark Pattern, Criminal Liability, Personal Data Protection.